Determination of Gartro-Somatic and Feeding Indices of Freshwater Crab Barytelphusa lugubris from Kathmandu, Nepal - Rana, Saroj (New Visions in Biological Science Vol. 3, 2021)
Gastro-somatic, feeding and vacuity indices of fresh water crab Barytelphusa lugubris were determined by collecting 692 crabs from Sangla Kunchi Pwakal, Village Development Committee, Kathmandu, Nepal from April 2007 to April 2008. The collected crabs were killed with chloroform and weighed. Crabs were dissected and complete alimentary canal was weighed. Then finally, only the contents from the stomach was removed, weighed and recorded. The seasonal and monthly gastro- somatic (GSI), feeding (FI) and vacuity indices were analyzed. The result indicated that the minimum and maximum (GSI) was (2.29) in summer (September) and (3.70) in spring (April 08) with significant fluctuations (p-value = 3.36e-12<0.05) for 13 months. Similarly, minimum and maximum FI recorded was (4.52) in autumn (November) and maximum (24.85) in spring (July) respectively. Similarly minimum and maximum vacuity index (VI) was (11.11) in spring (April, 2008) and (89.29) in autumn, (November). The mean coefficient of variance for gastro-somatic and feeding indices were 29.06% and 86.89% respectively. This indicates mores table GSI compared to FI.